Desiderium - Vance, Sydney (My University, 2022)
Desiderium is a collection of poetry composed with the aim of investigating loss through the primary lenses of grief and addiction. The poems housed in this collection attempt to navigate that opaque, precarious experience of developing an alcohol addiction/dependency while coming of age, and many of these poems specifically address the intersection of addiction, youth, and great tragedy. My work draws inspiration in storytelling technique from poets such as Ada Limón, Tracy K. Smith, and Maggie Smith. To write coherently and honestly about addiction, Kaveh Akbar’s Calling A Wolf A Wolf and sam sax’s madness were my foremost guides and influences. For my poems about grief, Mary Jo Bang’s Elegy was paramount; loss is naturally a heavy subject, and Bang’s work deftly demonstrates how grief can be written without the sacrifice of levity. The female body serving as one of my book’s foremost motifs, I have followed poets such as Natalie Diaz and Limón in my attempts to complicate how the body and the female sexual experience are transcribed. The greatest struggle I faced in the construction of Desiderium was in arranging the poetic order to align with the arc of my speaker in a way that feels purposeful and is coherent to the reader. Her journey is one that begins in a place of questioning and resistance in the first half, and ends in a place of more active acceptance and accountability for her life and her choices in the second. Ultimately, Desiderium is a record of young adulthood from this writer’s unique perspective, an attempt to make sense of fact, memory, and that barely perceptible space where the two intersect.
Keywords: Young women; Grief; Alcoholism; Poetry; Creative writing